"Justly Shall You Pursue Justice": Theological Approaches to Evaluative Injustice. Issue 4 (1st February 2022) - Muers, Rachel
Abstract: This article identifies and characterizes the phenomenon of evaluative injustice as the inequitable positioning of persons in relation to the activity of moral judgment, or the inequitable configuration of the space of moral judgment. The two main, closely interconnected, aspects of evaluative injustice are the disproportionate exposure of certain groups to moral judgment, and the disproportionate exclusion of certain groups from agency in moral judgment. Having argued that theology is significantly implicated in, and obligated to respond to, evaluative injustice, I outline a theological response to evaluative injustice through a reading of biblical texts on divine impartiality. The core focus should not be the abstract ideal of impartiality, but rather the role of "judges" and moral reasoners in recognizing and addressing pervasive social injustice.